2020
DOI: 10.5194/bg-17-1673-2020
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of forest biomass sampling strategies across scales

Abstract: Abstract. Tropical forests play an important role in the global carbon cycle as they store a large amount of carbon in their biomass. To estimate the mean biomass of a forested landscape, sample plots are often used, assuming that the biomass of these plots represents the biomass of the surrounding forest. In this study, we investigated the conditions under which a limited number of sample plots conform to this assumption. Therefore, the minimum number of sample sizes for predicting the mean biomass of tropica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Moreover, the inclusion of the 20 m radius plot data in the analysis avoids a bias in large tree stem numbers associated with using only the 20 m × 20 m square plots (Paul et al 2019) which is the reason it results in a reduction in our estimate of total carbon. Our use of larger plots also aligns us with research that identified smaller plot size as an issue when monitoring forest dynamics (Clark and Clark 2000;Wagner et al 2010;McMahon et al 2019;Hetzer et al 2020). Inclusion of these additional data also provided more precise estimates of carbon stocks and stock changes.…”
Section: Sampling and Methodological Considerationssupporting
confidence: 80%
“…Moreover, the inclusion of the 20 m radius plot data in the analysis avoids a bias in large tree stem numbers associated with using only the 20 m × 20 m square plots (Paul et al 2019) which is the reason it results in a reduction in our estimate of total carbon. Our use of larger plots also aligns us with research that identified smaller plot size as an issue when monitoring forest dynamics (Clark and Clark 2000;Wagner et al 2010;McMahon et al 2019;Hetzer et al 2020). Inclusion of these additional data also provided more precise estimates of carbon stocks and stock changes.…”
Section: Sampling and Methodological Considerationssupporting
confidence: 80%
“…However, a wider range of GPP values was observed in this study (0-40 Mg C ha −1 a −1 ) in comparison to MODIS product (values between 15 and 35). The data of Malhi et al [32] showed higher values than the average GPP determined in this study, but this was reasonable because their amount of included forest inventory data was rather low, the forest plots were much smaller in size than the resolution of the our map (1 km 2 ), and the locations of these forest plots were often in productive forests and not randomly selected [36]. , the MODIS-derived GPP product, and forest inventory data from Malhi et al [32] for the Amazon Basin.…”
Section: Gross Primary Productivitycontrasting
confidence: 44%
“…Indeed, determining the optimum sampling area depends on the manpower and material resources consumed by the field survey and the accuracy required by the investigators. Hetzer et al (2020) showed that 1 ha is the effective area for mean biomass estimation with sufficient precision in South America (Hetzer et al, 2020). We consider a sampling area of at least 140 × 140 m to reach the requirements for estimates of biomass productivity in this region (Figure 4 and Figure ), as the turning point in R 2 and rRMSE indicates the minimal scale for effective sampling is the above scale, sampling at a median scale may be more cost effective ( R 2 > 0.7, rRMSE <20%).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial heterogeneity of sampling units can cause difficulties for community surveys, but large sampling areas are fundamental for reflecting community characteristics. Indeed, determining the optimum sampling area depends on the manpower and material resources consumed by the et al (2020) showed that 1 ha is the effective area for mean biomass estimation with sufficient precision in South America (Hetzer et al, 2020). We consider a sampling area of at least 140 × 140 m to reach the requirements for estimates of biomass productivity in this region (Figure 4 previous research may have some problems.…”
Section: Accuracy Of the Rf Models At Different Scalesmentioning
confidence: 99%